2015
DOI: 10.1128/aac.00092-15
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm Peptides Increase the Susceptibility of Carbapenemase-Producing Klebsiella pneumoniae Clinical Isolates to β-Lactam Antibiotics

Abstract: dMultidrug-resistant carbapenemase-producing Klebsiella pneumoniae (KpC) strains are becoming a common cause of infections in health care centers. Furthermore, Klebsiella can develop multicellular biofilms, which lead to elevated adaptive antibiotic resistance. Here, we describe the antimicrobial and antibiofilm activities of synthetic peptides DJK-5, DJK-6, and 1018 against five KpC isolates. Using static microplate assays, it was observed that the concentration required to prevent biofilm formation by these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 40 publications
3
66
0
1
Order By: Relevance
“…Several other combinations of DJK-5 and DLK-6 with different antibiotics led to the eradication of P. aeruginosa , E. coli , A. baumannii , K. pneumoniae and S. enterica [18]. Intriguingly, Ribeiro et al demonstrated similar findings, reporting that peptide DJK-6 enhanced the activity of the β-lactam antibiotics meropenem, imipenem and cefepime to prevent biofilm formation by carbapenemase KpC-producing clinical isolates [39]. The combination of this peptide at 0.125 μg.mL −1 with only 0.06 μg.mL −1 of meropenem was capable of eradicating mature biofilms formed by these KpC isolates.…”
Section: Synthetic Antibiofilm Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other combinations of DJK-5 and DLK-6 with different antibiotics led to the eradication of P. aeruginosa , E. coli , A. baumannii , K. pneumoniae and S. enterica [18]. Intriguingly, Ribeiro et al demonstrated similar findings, reporting that peptide DJK-6 enhanced the activity of the β-lactam antibiotics meropenem, imipenem and cefepime to prevent biofilm formation by carbapenemase KpC-producing clinical isolates [39]. The combination of this peptide at 0.125 μg.mL −1 with only 0.06 μg.mL −1 of meropenem was capable of eradicating mature biofilms formed by these KpC isolates.…”
Section: Synthetic Antibiofilm Peptidesmentioning
confidence: 99%
“…Importantly, the peptides were shown to be non-toxic in the same invertebrate studies. In a parallel study performed by Ribeiro et al [39], it was demonstrated that DJK-6 was a promising peptide in preventing the formation of biofilms, as well as eradicating preexisting biofilms (at 2 – 4 μg.mL −1 ) formed by carbapenemase-producing K. pneumoniae clinical isolates (KpC isolates) [39]. …”
Section: Synthetic Antibiofilm Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilm formation by the C. albicans CI was assessed in BM2 minimal medium, consisting of 62 mM potassium phosphate buffer (pH 7.0), 7 mM (NH 4 ) 2 SO 4 , 2 mM MgSO 4 , 10 M FeSO 4 , and 0.5% glucose. The minimal biofilm inhibitory concentration to inhibit biofilm formation by 50% (MBIC 50 ) or 100% (MBIC 100 ) was assessed as described previously by Ribeiro et al (38). Briefly, after removal of planktonic cells, residual adherent cells were stained with 0.01% crystal violet for 20 min, and deionized water was used to wash microplate wells twice.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, these peptides represent a genuine antiresistance strategy for biofilm bacteria. Indeed, antibiofilm peptides were recently shown to reverse K. pneumoniae carbapenemase (KPC)-mediated resistance in K. pneumoniae, in that, e.g., 0.0625 g/ml meropenem combined with 0.125 g/ml DJK5 led to complete eradication of preexisting flow cell biofilms (40). …”
Section: Broad Spectrum Of Immunomodulatory Peptides With Antibiofilmmentioning
confidence: 99%